2022
DOI: 10.3168/jdsc.2021-0187
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bovine leukemia virus on dairy cow longevity

Abstract: Highlights• Dairy cows were tested for BLV with an ELISA milk test and followed for survival.• BLV-positive cows had shortened lifespans compared with BLV-negative herdmates.• BLV ELISA results were not associated with producer-reported reasons for culling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Epidemiologic studies on dairy cattle have demonstrated an association between BLV infection and decreased productive lifespan within herds [4,41,42], although others have not found this association [5,43]. Therefore, those findings should be further investigated in future studies for different cattle breeds, geographic areas, and management systems for animals with high vs. low proviral load.…”
Section: Discussionmentioning
confidence: 96%
“…Epidemiologic studies on dairy cattle have demonstrated an association between BLV infection and decreased productive lifespan within herds [4,41,42], although others have not found this association [5,43]. Therefore, those findings should be further investigated in future studies for different cattle breeds, geographic areas, and management systems for animals with high vs. low proviral load.…”
Section: Discussionmentioning
confidence: 96%
“…This increase has been particularly notable in areas from Canada and Argentina, resulting in significant economic losses ( John et al, 2024 ; Porta et al, 2023 ). In the United States, approximately 47.1 % of dairy cattle are affected, and 90 % of US dairy herds harbor at least one infected animal ( Benitez et al, 2022 ; LaDronka et al, 2018 ). Recent studies conducted across six different regions in Colombia have revealed prevalences ranging from 14 to 85 % among cattle, with BLV infection present in 75–100 % of the dairy and beef herds ( Corredor-Figueroa et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%